Pengembangan Kinerja Tenaga Pendidik Dalam Persiapan Pelaksanaan Kurikulum 2013 Di SD Muhammadiyah 10 Tipes Surakarta - Maharani Sheba, Aurora, Drs. Mulyadi S. K., SH.,M.Pd (2017)
Educators at the ELEMENTARY SCHOOL Muhammadiyah 10 Tipes holds an important role in the implementation of the curriculum in order to support the implementation of the 2013 learning at school. The purpose of this research is to identify the bottleneck that occurs in preparation for the implementation of the curriculum of 2013, describing educators preparedness to implement the curriculum of 2013, and identify how schools in developing educators for dealing with the implementation of curriculum 2013 in SD 10 Tipes of Muhammadiyah. This type of research is qualitative research. The primary source is the school principal, teachers and students. Secondary sources in the form of official documents and personal documentation by researchers. The technique of data collection by observation, interview and documentation. The validity of the data using triangulation of sources and methods. Data analysis techniques include the reduction of the data, the presentation of the data and draw conclusions. Preparation of obstructing the implementation of the curriculum in ELEMENTARY SCHOOL Muhammadiyah 2013 10 Tipes in preparation, implementation and assessment of the readiness factors caused by the teacher and an understanding of the concept of curriculum implementation of 2013. Educators preparedness factors affected by the competence of the teacher and the teacher's performance. Educators development program curriculum in preparation for 2013 could be implemented through teacher education programme, the role of the principal, socialization and training curriculum for 2013.